1999
DOI: 10.1002/(sici)1097-4547(19990615)56:6<668::aid-jnr13>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Selective subcellular redistributions of protein kinase C isoforms by chemical hypoxia

Abstract: The mechanisms of neuronal degeneration following hypoxia/ischemia remain undefined, but the processes include increases in neurotransmitter release, elevation of cytosolic-free calcium concentration, and changes in signal transduction pathways. Activation of the multigene family of protein kinase C (PKC) has been associated with the release of neurotransmitter and the survival of neurons. Therefore, to understand which PKC isozymes are involved in hypoxia/ischemia-induced neuronal degeneration, we examined PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…A confocal microscopy study of cPKC in the nucleus after LPS stimuli and an in vitro kinase assay and immunoprecipitation analysis using purified nuclear cPKC from LPS-treated RAW264.7 cells showed that cPKC can migrate into the nucleus and bind to HMGB1 after LPS stimuli to phosphorylate HMGB1 protein with an unknown mechanism. PKC isoenzymes are located in the cytoplasm as an inactive state in resting cells and are redistributed after stimuli (20,21), and the redistribution of PKC␣ and PKC␥ to the nucleus after PMA stimuli or hypoxic stress had been suggested in previous reports (47,48).…”
Section: Discussionmentioning
confidence: 75%
“…A confocal microscopy study of cPKC in the nucleus after LPS stimuli and an in vitro kinase assay and immunoprecipitation analysis using purified nuclear cPKC from LPS-treated RAW264.7 cells showed that cPKC can migrate into the nucleus and bind to HMGB1 after LPS stimuli to phosphorylate HMGB1 protein with an unknown mechanism. PKC isoenzymes are located in the cytoplasm as an inactive state in resting cells and are redistributed after stimuli (20,21), and the redistribution of PKC␣ and PKC␥ to the nucleus after PMA stimuli or hypoxic stress had been suggested in previous reports (47,48).…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, the extracellular and intracellular calcium chelation was also efficacious in blocking the induction of tolerance by NMDA preconditioning. We conjecture that a critical level of calcium is necessary to stimulate calcium-dependent enzymes, including PKC (Huang et al, 1999;Katsura et al, 1999) and nitric oxide synthase (Gonzalez-Zulueta et al, 2000;Nandagopal et al, 2001), that will lead to a signal transduction pathway that could ultimately play a role in neuroprotection.…”
Section: Discussionmentioning
confidence: 91%
“…Preparation of Membrane Fractions-Membrane fractions were prepared as described previously (27). Cells were washed twice with phosphate-buffered saline containing 2 mM EDTA and incubated on ice with extraction buffer (20 mM Tris, 2 mM EDTA, 5 mM EGTA, 10 mM mercaptoethanol, 0.1 mM PMSF, 5 g/ml leupeptin, and 5 g/ml aprotinin) for 10 min.…”
Section: Methodsmentioning
confidence: 99%